THE INFLUENCE OF ONLINE READING ON FACEBOOK AND MOTIVATION TOWARD NARRATIVE READING ACHIEVEMENT OF THE EIGHTH GRADE STUDENTS OF MUHAMMADIYAH JUNIOR HIGH SCHOOL 7 OF PALEMBANG IN ACADEMIC YEAR OF 2013/2014 - Nozylianty Nozylianty (Esteem Journal of English Education Study Programme, 2019)
Reading text in a second or foreign language is more difficult than in the first language. The research questions in this research: Is there any significant difference in online reading on Facebook to ward narrative reading achievement that are thought by using guided reading comprehension? Is there any significant difference in online reading on Facebook toward narrative reading achievement in high motivation? Do online reading on Facebook and motivation toward narrative reading achievement affect to the students’ narrative reading comprehension? The results of the research are: It was found the significant level (2tailed) was 0.000 since 0.000 < 0.05 it means that the students’ narrative reading text on Facebook and motivation in experimental group after applying guided reading increased significantly and was used effective to be taught in a certain group. And there is any influence, and improvement of online reading on Facebook and motivation toward narrative reading achievement. From the probability hypothesis table in SPSS Version 21 the output 0.000 < 0.05 so the HO is ejected and Ha is accepted. Facebook can also be used for teaching other subjects such as speaking and structure. It is important that they must be able to motivate learners to think mentally and psychologically. Besides, the learners are supported to solve problems, to interact with each others, and to learn perpetually as well as consistently. Facebook give the effects and influences, as a strategy and also technique for the English teachers had positive and negative feedback for the students